2007
DOI: 10.4314/bcse.v21i2.21200
|View full text |Cite
|
Sign up to set email alerts
|

<b>DETERMINATION OF FREE CYANIDE AND TOTAL CYANIDE CONCENTRATIONS IN SURFACE AND UNDERGROUND WATERS IN BOGOSO AND ITS SURROUNDING AREAS IN GHANA</b>

Abstract: Concentrations of free cyanide and total cyanide in water samples in Bogoso and its surrounding areas in Ghana have been measured in this study. Concentrations of free cyanide and total cyanide were found to be above the maximum permissible discharge limit of effluent from mining companies into natural waters set by Environmental Protection Agency, Ghana (GEPA). A comparison of the results obtained in this study with permissible levels set by US Environmental Protection Agency and the World Health Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…To obtain crude protein value, nitrogen content values were multiplied by a factor of 6.25. For cyanide determinations, the method was in accordance with Obiri et al (2007).…”
Section: Chemical Analysismentioning
confidence: 99%
“…To obtain crude protein value, nitrogen content values were multiplied by a factor of 6.25. For cyanide determinations, the method was in accordance with Obiri et al (2007).…”
Section: Chemical Analysismentioning
confidence: 99%
“…According to these guidelines, the free cyanide concentrations were found to be in safe levels owing to the low evaporation rates of cyanide in the water resources. The free cyanide concentration recorded in the present study was relatively lower than those found in the surface water of Obuasi area (Ndur and Amegbey 2013) and Bogoso (Obiri et al 2007), all in Ghana owing to extreme gold mining activities in these areas. There was a significant difference (p < 0.05) in free cyanide levels between the dam and borehole water samples.…”
Section: Resultsmentioning
confidence: 51%
“…The cyanide concentration is higher in red blood cells than in plasma by a factor of two or three, reflecting cyanide's tendency to bind with methaemoglobin. Cyanide may also accumulate in body cells by binding with metalloproteins or enzymes such as catalyses or cytochrome c oxidase [8][9][10]. The most important sources of cyanide pollution in the surface water is through mining operations and industrial and agricultural activities [5,[10][11].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cyanide may also accumulate in body cells by binding with metalloproteins or enzymes such as catalyses or cytochrome c oxidase [8][9][10]. The most important sources of cyanide pollution in the surface water is through mining operations and industrial and agricultural activities [5,[10][11]. Thus this study focuses on the evaluation of free and total cyanide levels and their concentrations and distribution in water in order to know the sources of contaminants in the aquatic system.…”
Section: ■ Introductionmentioning
confidence: 99%